Evaluation of Acceptance of Non-Communicable Disease Information System Applications Based on User Experience - Indah Naryanti; Farid Agushybana; Eko Sediyono; Cahya Tri Purnami; Aris Puji Widodo (Community Medicine and Education Journal, 2022)
The mortality rate due to non-communicable diseases (PTM) in Indonesia is higher than the global death rate. The non-communicable disease information system (SI-PTM) was created to assist programmers in facilitating their work. This study aims to evaluate the acceptance of the information system needed to determine the user's desire to use the SI-PTM. This research is an observational study. Respondents in this study were Semarang City Health Center officers who were appointed as operators of the non-communicable disease information system (SI-PTM). Data were collected using a questionnaire containing the technology acceptance model (TAM) indicators. This analysis aims to describe user acceptance of SI-PTM as well as maturity level using TAM indicators, namely perceptions of usefulness, perceived convenience, attitudes, and intentions to use information systems. In conclusion, the majority of respondents stated that non-communicable disease information systems provide benefits in facilitating reporting and monitoring of non-communicable disease cases in the city of Semarang.